Numerical experiment of radiation self-absorption and radiation dynamics in the dense plasma focus using Lee model - Ali, Zahra (2013)
Radial dynamics and plasma focus pinch were influenced in slow compression mode by optically thick plasma due to radiation self-absorption. In this study, the role of radiation self-absorption in Mather type dense plasma focus (DPF) device was investigated. The impact of opacity in slow compression phase and the behaviour of optically thick plasma towards radiation emission were explored. The numerical modelling of self-absorption effect on radiation dynamics, focusing, cooling, collapse and influence of self-absorption on the radiation emission was performed. Lee Model was used for numerical simulation. The model was developed incorporating the various energy balances including thermodynamics, kinematics, radiation dynamics and was capable of yielding the plasma structure and trajectories. The snowplow model describes the axial rundown phase and slug model in radial phase of pinch. Numerical simulations were performed for the absorption of radiation within dense and optically thick plasma. It was found that a steady state pinch with constant radius was only possible at the Pease–Braginskii (PB) current of 1.2 to 1.6 MA for hydrogen and deuterium DPF. For lower and higher values of input current as compared to PB current, the pinch expands and collapses respectively. This current was reduced for heavier gases like Neon (Ne), Argon (Ar), Krypton (Kr) and Xenon (Xe) due to the emission of significant amount of line radiation. For Ne, Ar, Kr and Xe gases with different DPF configurations more severe radiative collapse was observed as compared without the self-absorption factor. It was found that for Ar with no self-absorption, the pinch boundary collapsed in only a few nanoseconds to the radius of 0.1 mm set as cut-off in the model. The pinch does not attain the cut-off radius with self-absorption. In the case of Ne, there was no radiative collapse with self-absorption factor but radiative collapse occurs without self-absorption. A severe radiative collapse was also observed in both cases of Kr and Xe. It was inferred that the pinch radius collapses less when self-absorption was taken into account. The plasma opacity reduces the amount of radiation loss. Thus, self-absorption phenomenon was significant during the slow compression phase and needs to be considered in the design of a new DPF device.